PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Ryad, Ahmad Muhammad; Syahrul, Muhammad; Istiqomah, Iin; Febriyanti, Rahma; Silpiani, Epi (LPPM STIE Muhammadiah Bandung, 2024)
Financial reporting standards have flexibility in determining the methodology and accounting principles of each company, but there are vulnerabilities in the methodology and principles that can be manipulated to obtain various profits. The purpose of this study is to determine whether earnings management is influenced by corporate governance moderated by the value of the company in telecommunications companies during the period 2017 to 2022. The samples in this study were 15 telecommunications companies listed on the IDX during the period 2017 to 2022. The data used is panel data, which is a combination of time series and cross section data. The software used is Smart-PLS 04 using path analysis partial least square (PLS) technique outer model for model testing and inner model for structural model testing. The results obtained are that corporate governance has no effect on earnings management. Corporate governance has no effect on firm value, firm value has no effect on earnings management. And company value does not mediate the effect of corporate governance on earnings management.